Changing concepts of risk, security and war - Pertti Joenniemi; Kristian Søby Kristensen; Karen Lund Petersen (Danish Institute for International Studies (DIIS), 2007)
It is commonplace to argue speed as the deflning element in modern day warfare. Whether one looks to the manuals and concepts of the US military or to critical thinkers like Virilio the analvsis is the same. Speed and time, not mass and space, are the essentials of warfare. This is the case in the analysis of both the Western high-tech militaries and their asymmetrical terrorist opponents. This paper argues, by heuristically applying Zygmunt Baumann's concepts of tourist and vagabond, that exactly the making of space can be seen as the centre of gravity in the 'Global War on Terror'. Whether you are able to act as a detached and forever moving tourist or as a vagabond limited by imposed space and boundaries will deflne success or failure in this global war. Space has thus not lost its importance; conditioned by its relationship to time it has become a weapon that wins wars.
Keywords: 330; Politische Gewalt; Risiko; Krieg; Sicherheitspolitik